hansen.app: Simplified Neurological Assessment Form Application for Data Collection to Support Hansen’s disease Treatment - Militão, Anthony Alexandre Morais; Silva, Anna Beatriz; Masson, Gabriel; Morais, Cleber Matos de; Endo, Patricia Takako (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
This study addresses the challenge of improving Hansen’s disease understating and monitoring in Brazil’s public healthcare system (SUS) through the development of a digital record system rooted in Soft Systems Methodology (SSM). The proposed solution, the hansen.app, integrates participatory cycles with real stakeholders to adapt and digitize the Simplified Neurological Assessment (from Portuguese ANS) form, ensuring data fidelity and enhanced usability for healthcare professionals and patients. Hence, data modeling and the prototype aim to reduce the complexity of Hansen’s disease care and monitoring by delivering more essential data to improve the knowledge capacity of the healthcare system.